Summer Health-Improving Campaign as a SocioLegal Policy Tool of a State - Konin, Nikolai; Bogdanova, Tatyana; Ilgova, Ekaterina; Kuznetsova, Irina; Gorbachev, Mikhail (International Journal of Psychosocial Rehabilitation, 2020)
Analysis of summer health-improving campaign arrangements allows assessing the efficiency of work of bodies and institutions of the child neglect and delinquency prevention system during the period of children’s summer holidays. The article aims at studying the specificity of organizing and carrying out a summer health-improving campaign (SHIC) as one of the tools of state social policy implementation. Statistics methods, variation series in particular, were used as the main method of analysis. In some cases, there was not enough data on average index of this or that indicators allowing assessing specificity of organizing and carrying out SHIC. Then conclusions and generalisations were carried out on the basis of variation or dispersion of distinct indicator index which is also an important characteristic of the complex studied. An additional method was a comparative-competitive approach. Regularity of SHIC carrying out in district RF constituents was revealed. Typical tendencies and the specificity of unique regional experience in organizing summer health-improving campaign were identified. The research resulted in obtaining regional models of organizing and carrying out SHIC, oriented both at federal experience and at particular socio-cultural and economic specificity of RF constituents.